The Influence of Health Service Quality Dimensions on the Satisfaction Level of Inpatients at Cut Nyak Dhien General Hospital Langsa City - Putri Riskina; Megawati Megawati (Journal of Educational Innovation and Public Health, 2026)
The dimensions of healthcare service quality are a concept for measuring service quality. This study aims to determine the effect of the dimensions of healthcare service quality on the satisfaction of inpatients at Cut Nyak Dhien General Hospital in Langsa City. This study uses a quantitative design of the Survey Analytic type with a cross-sectional approach. The population consisted of 121 inpatients with a sample size of 55 respondents using purposive sampling technique. Analysis used multiple logistic regression test (α=0.05). The research results show that there is an influence between Responsiveness p<0.042 with an EXP (B) value of 11.361, Assurance p<0.008 with an EXP (B) value of 20.163, Empathy p<0.018 with an EXP (B) value of 13.547, Reliability p<0.033 with an EXP (B) value of 6.896 on inpatient patient satisfaction (p<0.05), while the Tangible variable shows no influence with p<0.088 and an EXP (B) value of 4.967. Among these variables, the one that significantly affects inpatient patient satisfaction is the Assurance variable with p<0.008 and an EXP (B) value of 20.163. It is recommended to continuously improve the quality of service comprehensively in every dimension of service quality, strengthen the competence and professionalism of healthcare personnel, enhance the speed and accuracy of service, and build good communication to improve the quality of inpatient services and maintain patient trust in the hospital.